2015
DOI: 10.1152/ajpendo.00182.2014
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity exacerbates metabolic and behavioral effects of polycystic ovary syndrome in a rodent model

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy affecting women of reproductive age. Although a comorbidity of PCOS is obesity, many are lean. We hypothesized that increased saturated fat consumption and obesity would exacerbate metabolic and stress indices in a rodent model of PCOS. Female rats were implanted with the nonaromatizable androgen dihydrotestosterone (DHT) or placebo pellets prior to puberty. Half of each group was maintained ad libitum on either a high-fat diet (HFD; 40% butter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 57 publications
2
19
0
1
Order By: Relevance
“…The model has a number of clinical and pathological features in common with obese patients with PCOS, such as obesity, hyperinsulinemia, hyperandrogenism, ovarian follicle immaturity, and ovulation disorders (37, 38). Compared with the control group (CON; normal diet), the HF group had significantly higher body mass and prominent hyperinsulinemia.…”
Section: Resultsmentioning
confidence: 99%
“…The model has a number of clinical and pathological features in common with obese patients with PCOS, such as obesity, hyperinsulinemia, hyperandrogenism, ovarian follicle immaturity, and ovulation disorders (37, 38). Compared with the control group (CON; normal diet), the HF group had significantly higher body mass and prominent hyperinsulinemia.…”
Section: Resultsmentioning
confidence: 99%
“…However, the specific role of androgens and the mechanisms underlying these complications are largely unknown. Studies in female rodents have demonstrated that continuous exposure to androgens (testosterone or DHT) increases anxiety-like behavior (23,24), but studies of androgens and anxietylike behaviors in males have yielded inconsistent findings (25) and show either anxiolytic (26)(27)(28) or anxiogenic effects (29).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the level of cytokines and MDA are also higher in obese PCOS compared to obese non-PCOS women, although both have higher TNFα and MDA levels than lean PCOS and lean controls (Alshammari et al 2017, Artimani et al 2018. These data suggest that PCOS exacerbates obesity-dependent ovarian inflammation and oxidative stress (Ressler et al 2015). Distinct metabolic differences between obesity and PCOS include hyperandrogenemia, that is, obese women without PCOS have circulating total testosterone concentrations similar to lean control women (Keskin Kurt et al 2014, Alshammari et al 2017, Usta et al 2018.…”
Section: Metabolic and Ovarian Phenotypes Of Pcosmentioning
confidence: 99%